Computational study to assess the influence of overlap ratio on static torque characteristics of a vertical axis wind turbine - Roy, Sukanta; Saha, U. (2013)
This paper presents an unsteady two-dimensional computational study in order to observe the effect of overlap ratios on static torque characteristics of a vertical axis wind turbine (VAWT). The study is performed with the help of a finite volume based computational fluid dynamics (CFD) software package Fluent 6.3. The computational model is a two-bladed conventional VAWT having overlap ratios of 0, 0.10, 0.15, 0.20, 0.25 and 0.30. Initially, a comparative analysis is made using various k-e turbulence models and then the results are compared with the experimental data available in literature. A realizable k-e turbulence model with enhanced wall treatment is found suitable for further computational analysis. The flow field around the turbine model is also studied with the help of static pressure contour analysis. Based on this computational study, it is realized that an overlap ratio of 0.20 eliminates the effects of negative static torque coefficient, provides a low static torque variation at different turbine angular positions and also gives a higher mean static torque coefficient as compared to the other overlap ratios.